«The womb of tradition» (some reflections about an image-concept) - Pysarenko, Yurii (Actual Problems of Mind, 2017)
An image-bearing concept of the «womb of tradition» indicates the connection between mother and child as a model for tradition. This very connection between mother and child considered as historically the first element of social life can be taken as a beginning of an historical transfer of tradition. Psychologically adhering to the tradition can be treated as an aspiration to return to the «mother womb», what is reflected in various transitional rituals.